Bouncing and bending light - Taylor, Barbara, 1954-; Millard, Peter (New York ; London : F. Watts, 1990)
Presents projects and experiments demonstrating the effects of mirrors and lenses on rays of light.
4.9
3-6
School Library Journal
Booklist
Keywords: Light -- Experiments -- Juvenile literature; Reflection (Optics) -- Experiments -- Juvenile literature; Mirrors -- Experiments -- Juvenile literature; Lenses -- Experiments -- Juvenile literature; Light -- Experiments; Reflection (Optics) -- Experiments; Mirrors -- Experiments; Lenses -- Experiments; Experiments